Nodular sclerosing Hodgkin's lymphoma with breast involvement: Case report and review of the literature - Modi, Yashpal (Medknow Publications & Media Pvt Ltd, 2014)
Extranodal disease in Hodgkin's lymphoma (HL) is very rare and it occurs in 15-30% of all cases. The intrathoracic area is the most common extranodal presentation. There are very few cases in the medical literature of breast involvement with HL. We report a 25-year-old woman who had been managed and treated for nodular sclerosing HL for 6 months, but she was noncompliant with chemotherapy. She presented 1 year later with a palpable left breast mass and B symptoms. The fluorine-18 fluorodeoxyglucose-positron emission tomography images revealed disseminated disease with a left breast mass demonstrating fluorodeoxyglucose uptake. Histopathology of the ultrasound-guided biopsy specimen of the breast mass was consistent with recurrence. This case highlights the need for an awareness of HL presenting in this way because the diagnosis has therapeutic and prognostic implications.